Representasi Lingkungan dalam Sastra Indonesia: Tinjauan Literatur Review - Pamungkas, Onok Yayang; Hastangka, Hastangka; Sudigdo, Anang; Fathonah, Siti; Fauzan, Akhmad; Suroso, Eko (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
The current environmental crisis is an important issue that is the focus of research globally, including in Indonesia. Therefore, this research is an effort to explore trends in environmentally sound literary research in Indonesia. The research process was carried out by combining statistical data combined with descriptive analysis. Therefore, mixed-method research methods are considered appropriate to use. Research data is a source of literary ecology research trends taken from the Google Scholar database. The data source is Google Scholar. Data retrieval using the Publish or Perish app. The data is taken by entering the keyword